Lightweight compression-resistant heat-insulating noise-reducing material as well as preparation method and application thereof
By using coal-based solid waste and high-temperature foaming agents and other materials, high-performance lightweight compressive insulation and noise reduction materials are prepared, which solves the problems of low porosity and low mechanical properties of porous insulation materials, and achieves performance Improve and simplify production processes.
Patent Information
- Application Number
- CN202411942584.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-02-14
AI Technical Summary
The existing porous thermal insulation materials have problems with low sample porosity and low mechanical properties, and the production process process is complex and the cost is high.
Coal-based solid waste such as coal gangue and fly ash is used as the main raw materials, and by adding high-temperature foaming agent and flux, a density of 0.16-0.4 g/cm3, compressive strength of 1-6 MPa, porosity of 70-85 is prepared. % lightweight compressive insulation and noise reduction material.
The material's porosity is improved, compressive strength is enhanced, thermal conductivity is reduced, and sound absorption coefficient is improved. The production process is simplified and the cost is reduced. Its performance is better than that of traditional exterior wall partition materials and rock wool and other sound absorption materials.
Smart Images

Figure CN119431001A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of building thermal insulation and noise reduction materials, and in particular relates to a lightweight compression-resistant thermal insulation and noise reduction material and a preparation method and application thereof. Background Art
[0002] At present, there are many types of building insulation materials used in China, including expanded perlite, mineral wool, organic thermal insulation materials, inorganic thermal insulation materials, etc. Expanded perlite can expand rapidly to dozens of times its original volume at high temperature. Since the thermal insulation materials prepared by it have low thermal conductivity, good fire resistance and sound insulation effects, they are mostly used in building insulation materials. However, expanded perlite has strong hydrophilicity, which causes the thermal conductivity to drop sharply after contacting water. Mineral wool is produced by blowing molten slag to form fibers. Its excellent thermal insulation performance was used in building insulation materials in the early stage, but most mineral wool contains asphalt and other organic matter, which will produce a large amount of harmful substances during use. Organic thermal insulation materials are a common thermal insulation material today. They usually have the characteristics of light weight, good sound insulation effect, and do not require too high a roasting temperature. However, they are obviously insufficient in fire resistance and durability, and a large amount of expensive raw materials are required in the production process, resulting in low economic efficiency.
[0003] Inorganic thermal insulation materials have the characteristics of light weight, no decay, high temperature resistance, etc., and are mainly used in the field of building thermal insulation materials. Due to the advantage of large slag consumption in the preparation process of inorganic porous thermal insulation materials, it has become a research hotspot to use silicate structure as raw material, add a certain amount of foaming agent, flux and other additives, and then evenly mix and sinter at high temperature to obtain porous thermal insulation materials. Porous thermal insulation materials are a new type of functional material with the advantages of light weight, sound insulation, large specific surface area, good chemical stability, low dielectric constant, and low thermal conductivity.
[0004] The Chinese patent publication number CN 106478124 A, entitled "A method for preparing a porous carbon thermal insulation composite material", discloses that an ionic liquid is used as a carbon precursor, and a carbon fiber reinforced porous carbon thermal insulation composite material is obtained by a molten salt method under high pressure. The disadvantage of this patent technology is that the production process is complicated, the production cycle is 3 to 5 days, and it needs to be sintered in a high-pressure inert gas environment (1 to 10 MPa) to form a carbon skeleton. The Chinese patent publication number CN101723701A, entitled "A method for preparing a porous thermal insulation material of a titanate", discloses that a porous thermal insulation material of a titanate is obtained by sintering and washing at 650 to 1300 °C with potassium hexatitanate as a raw material. The disadvantage is that the porosity of the prepared material sample is only 5% to 55%. Chinese patent publication number CN108484119A, entitled "Lightweight thermal insulation material and preparation method thereof", discloses the preparation of lightweight porous thermal insulation material using construction waste as raw materials. The disadvantage of this patent method is that the mixed wet materials need to be pressed and formed under high pressure conditions of 10~15MPa.
[0005] In summary, the existing porous thermal insulation materials have the problems of low sample porosity and low mechanical properties, as well as complex production process and high cost. Summary of the invention
[0006] In order to solve the problems of low sample porosity and low mechanical properties of existing porous thermal insulation materials, as well as the complex process flow and high cost of the production process, the present invention proposes a technical route for preparing high-performance lightweight thermal insulation materials using coal gangue, fly ash and other coal-based solid wastes as the main raw materials. The preparation method of the lightweight pressure-resistant thermal insulation material of the present invention is based on the chemical composition of raw materials such as coal gangue and fly ash to determine the corresponding ratio of auxiliary materials and external additives that need to be added, and the corresponding blank forming method and sintering process conditions are determined according to the performance requirements of the lightweight thermal insulation material. By adding a small amount of high-temperature foaming agent and flux to the formula, pores are introduced into the ceramic matrix, the density of the ceramic is reduced, and a uniform, closed small pore structure is obtained, thereby improving the porosity of the porous thermal insulation material.
[0007] The technical scheme of the present invention for achieving the above-mentioned object is as follows.
[0008] A lightweight compression-resistant heat-insulating noise-reducing material, characterized in that the density of the lightweight heat-insulating noise-reducing material is 0.16-0.4 g / cm 3 , compressive strength is 1-6 MPa, porosity is 70-85%, thermal conductivity is not higher than 0.12 W / (m‧K), and sound absorption coefficient is above 0.78; The lightweight heat-insulating and noise-reducing material is prepared by mixing industrial solid waste, auxiliary materials and / or additives according to certain mass fractions, and then subjecting the mixture to ball milling, green body forming and high-temperature sintering; wherein the mass fraction ratio of industrial solid waste, auxiliary materials and / or additives is 50-100:20-40:0-10.
[0009] The industrial solid waste is industrial solid waste A, or a mixture of industrial solid waste A and industrial solid waste B; when the mass ratio of industrial solid waste A to industrial solid waste B in the industrial solid waste is 50~80:0~40.
[0010] The industrial solid waste A is a mixture of one or two of coal gangue, gasified slag or fly ash in any proportion; the industrial solid waste B is a mixture of one or more of waste glass, iron tailings or silica fume in any proportion. Before use, both industrial solid waste A and industrial solid waste B need to be repeatedly crushed and ground to a particle size greater than 200 mesh.
[0011] The auxiliary material is a raw material rich in alkali metal and alkaline earth metal oxides, preferably one or a mixture of any proportion of diatomaceous earth, albite, dolomite, talc or silica fume, wherein the particle size of diatomaceous earth, albite, dolomite, talc or silica fume is 200 mesh to 500 mesh.
[0012] The additive includes one or more of silicon carbide, sodium phosphate, polyvinyl alcohol, borax, sodium carbonate, and basic magnesium carbonate. When the additive is silicon carbide SiC, the purity is 99.9%, the particle size is 300 mesh to 1000 mesh, and the addition amount is preferably 0.4 to 2 parts by weight.
[0013] When the additive is sodium phosphate Na3PO4, the purity is analytically pure and the added amount is preferably 0 to 4 parts by weight.
[0014] When the additive is polyvinyl alcohol, the purity is analytically pure and the added amount is preferably 0 to 5 parts by weight.
[0015] The preparation method of the lightweight pressure-resistant heat-insulating noise-reducing material of the present invention comprises the following steps: 1) Batching: According to the chemical composition of industrial solid waste A, determine the selection and batching ratio of industrial solid waste A, industrial solid waste B, auxiliary materials and additives, and then weigh the required mass of industrial solid waste, auxiliary materials and additives according to the determined formula ratio and mix them evenly.
[0016] 2) Ball milling: dry ball milling is performed until the particle size of the mixed raw materials is D90 < 45 μm to obtain a uniformly mixed powder; wherein the grinding medium is agate balls, the mass ratio of agate balls to the mixed materials is 1:1, and the ball milling speed is 200~500 rpm.
[0017] 3) Blank body forming: spray-dry the powder and then prepare a shaped blank by a stacking method; wherein the step of preparing the shaped blank by the stacking method is: spray-dry the powder obtained in step 2) and then dry it to constant weight to obtain particles with uniform particle size, transfer them to a mold, scrape the surface to obtain a shaped blank.
[0018] 4) High temperature sintering: The green body is sintered in an air atmosphere, the temperature is raised from room temperature to 1100 ℃ at 3~8 ℃ / min, and kept warm for 10~30 min, and the temperature is raised from 1100 ℃ to 1120~1230 ℃ at 0.5~5 ℃ / min, and kept warm for 5~60 min, and then naturally cooled to room temperature to obtain a lightweight, compressive, heat-insulating and noise-reducing material.
[0019] Compared with the prior art, the present invention has the following advantages: (1) Coal-based solid waste such as coal gangue or fly ash is used as the main raw material for preparation. The utilization rate of coal gangue is as high as 70%. On the one hand, it reduces the high cost and high energy consumption of the existing traditional lightweight pressure-resistant porous material preparation process using high-value oxides as raw materials. On the other hand, it solves the resource utilization of coal-based solid waste and turns waste into treasure.
[0020] (2) The lightweight, pressure-resistant, heat-insulating and noise-reducing material prepared by the present invention adopts a stacking method. After the solid waste such as coal gangue is crushed and processed, it is only necessary to ball-mill and mix the various raw materials and obtain a sintering precursor through simple pretreatment. The production process is simple and the production cycle is shortened.
[0021] (3) The porosity of the lightweight compression-resistant heat-insulating and noise-reducing material prepared by the present invention is 70-85%, the compressive strength is greater than 1 MPa, the thermal conductivity is less than 0.12 W / (m‧K), and the sample parameters are better than the performance indicators of exterior wall partition materials (T / CBCSA 12-2019); the sound absorption coefficient of the samples is greater than 0.78, which is better than the performance of traditional sound-absorbing materials such as rock wool, and has high flame retardancy. The material of the present invention has good comprehensive properties and can be used as a thermal insulation, heat insulation and noise reduction material, and can be widely used in construction, transportation, aerospace and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the XRD spectrum of the lightweight compression-resistant, heat-insulating and noise-reducing material sample prepared in Example 1.
[0023] Figure 2 This is the morphology and pore structure distribution diagram of the lightweight compression-resistant, heat-insulating and noise-reducing material sample prepared in Example 3. DETAILED DESCRIPTION
[0024] The present invention is further described in detail below with reference to the embodiments. Example 1
[0025] The raw material composition and mass ratio of the material are 70% coal gangue, 20% diatomaceous earth and 10% talc, and the added amount of silicon carbide accounts for 0.6% of the total raw material mass, among which the coal gangue is crushed and screened to more than 200 meshes.
[0026] The above raw materials were mixed and then dry-milled for 32 h at a ball milling speed of 300 rpm. The ball-milled powder was dried and loaded into a corundum porcelain boat covered with fiber paper, and then placed in a muffle furnace for high-temperature sintering. The temperature was raised from room temperature to 1100 ℃ at 5 ℃ / min, kept warm for 20 min, and then raised to 1190 ℃ at 1 ℃ / min, kept warm for 25 min. After natural cooling, a lightweight, compressive, heat-insulating and noise-reducing material was obtained.
[0027] The compressive strength of the above materials was tested by a computer-automatic constant stress testing machine. The water absorption and porosity of the samples were determined by the Archimedes drainage method and the pycnometer method. The thermal conductivity of the samples was tested by the transient plane heat source method. The sound absorption coefficient was determined by the standing wave ratio method. The test results are shown in Table 1.
[0028] Figure 1 The XRD spectrum of the sample of Example 1 shows that the main phases of the sample are cordierite phase and quartz phase, wherein the cordierite phase has the characteristics of low dielectric constant and high mechanical strength, so that the sample has the characteristics of low thermal conductivity and high compressive strength. Example 2
[0029] The raw material composition and mass ratio are 73% coal gangue, 18% waste glass and 1% silicon carbide, the added amount of polyvinyl alcohol accounts for 5% of the total raw material mass, and the added amount of Na3PO4 accounts for 3% of the total raw material mass. The coal gangue and waste glass are crushed and sieved to more than 200 meshes.
[0030] The above raw materials were mixed and then dry-milled for 8 h at a ball milling speed of 280 rpm. The ball-milled powder was dried and loaded into a corundum porcelain boat covered with fiber paper, and then placed in a muffle furnace for high-temperature sintering. The temperature was raised from room temperature to 1100 ℃ at 5 ℃ / min, kept warm for 30 min, and then raised to 1140 ℃ at 3 ℃ / min, kept warm for 40 min. After natural cooling, a lightweight, compressive, heat-insulating and noise-reducing material was obtained.
[0031] The test was carried out using the method in Example 1, and the test results are shown in Table 1. Example 3
[0032] Material raw material composition and mass ratio: 65% coal gangue, 5% waste glass, 10% albite, 10% dolomite and 10% talc, the addition of silicon carbide accounts for 1% of the total raw material mass, and the addition of polyvinyl alcohol accounts for 5% of the total raw material mass. The coal gangue and waste glass are crushed and sieved to more than 200 meshes.
[0033] The above raw materials were mixed and then dry-milled for 8 h at a ball milling speed of 320 rpm. The powder after ball milling was sprayed to obtain particles with uniform particle size after drying. The particles were loaded into a corundum porcelain boat covered with fiber paper, the surface was scraped flat, and the particles were placed in a muffle furnace for high-temperature sintering. The temperature was increased from room temperature to 1100 ℃ at 5 ℃ / min, kept warm for 10 min, and then increased to 1210 ℃ at 1 ℃ / min, kept warm for 15 min, and naturally cooled to obtain a lightweight, compressive, heat-insulating and noise-reducing material.
[0034] The test was carried out using the method in Example 1, and the test results are shown in Table 1.
[0035] The pore structure of the sample in Example 3 was statistically analyzed, and the results are as follows: Figure 2 As shown, it can be seen that the average pore size of the sample is as small as 2.02 mm, the pore size distribution range is 1.3-2.8 mm, the pore size probability range is above 95%, the pore structure is spherical and evenly distributed, and the sample has a high porosity and excellent sound absorption performance. Example 4
[0036] Material composition and mass ratio of raw materials: 50% coal gangue, 10% fly ash, 10% iron tailings, 30% silica fume, and the amount of silicon carbide added accounts for 1% of the total raw material mass, among which: coal gangue is crushed and screened to more than 200 mesh, and iron tailings are crushed and ground to less than 200 mesh.
[0037] The above raw materials were mixed and then dry-milled for 8 h at a ball milling speed of 400 rpm. The ball-milled powder was dried and loaded into a corundum porcelain boat covered with fiber paper, and then placed in a muffle furnace for high-temperature sintering. The temperature was increased from room temperature to 1100 ℃ at 5 ℃ / min, kept warm for 10 min, and then increased to 1200 ℃ at 2 ℃ / min, kept warm for 20 min, and naturally cooled to obtain a lightweight, compressive, heat-insulating and noise-reducing material.
[0038] The test was carried out using the method in Example 1, and the test results are shown in Table 1.
[0039] Table 1 Performance of lightweight compression-resistant, heat-insulating and noise-reducing materials prepared by the present invention Example <![CDATA[Density (g / cm 3 ).]]> Porosity (%) Compressive strength (MPa) Thermal conductivity W / (m‧K) Sound absorption coefficient 1 0.40 80.6 5.91 0.106 0.92 2 0.69 71.7 4.72 — 0.78 3 0.35 84.9 2.47 0.114 0.96 4 0.22 72.8 1.47 0.112 0.87 .
[0040] It can be seen from Table 1 that the porosity of the material prepared in Example 2 is relatively low, and the sound absorption coefficient is also correspondingly low. Although the heat insulation and noise reduction performance is not very ideal, it still maintains a relatively high compressive strength; while the lightweight compressive heat insulation and noise reduction materials prepared in the other examples are rich in pores, and the density distribution is 0.22-0.40 g / cm 3The compressive strength can reach 5.91MPa, and the sound absorption coefficient is above 0.78. In the preferred embodiment, the sound absorption coefficient reaches 0.87-0.96, indicating that the method of the present invention can obtain a multifunctional porous material with compression resistance, heat insulation and noise reduction functions, and the sample parameters are better than the performance indicators of exterior wall partition materials (T / CBCSA 12-2019) and the performance of traditional sound-absorbing materials such as rock wool. It has good comprehensive performance and can be used as a high-quality compression resistance, heat insulation / insulation and noise reduction material in construction, transportation, aerospace and other fields.
[0041] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification or equivalent change made to the above embodiment based on the technical essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A lightweight, pressure-resistant, heat-insulating, and noise-reducing material, characterized by: Density 0.16-0.4 g / cm 3 , compressive strength is 1-6MPa, porosity is 70-85%, thermal conductivity is not higher than 0.12 W / (m‧K), and sound absorption coefficient is above 0.78; The lightweight heat-insulating and noise-reducing material is prepared by mixing industrial solid waste, auxiliary materials and / or additives according to certain mass fractions, and then subjecting the mixture to ball milling, green body forming and high-temperature sintering; wherein the mass fraction ratio of industrial solid waste, auxiliary materials and / or additives is 50-100:20-40:0-10.
2. The lightweight pressure-resistant, heat-insulating and noise-reducing material according to claim 1 is characterized in that: The industrial solid waste is industrial solid waste A, or a mixture of industrial solid waste A and industrial solid waste B; when the mass ratio of industrial solid waste A to industrial solid waste B in the industrial solid waste is 50~80:0~40.
3. The lightweight pressure-resistant, heat-insulating and noise-reducing material according to claim 1 is characterized in that: The industrial solid waste A is a mixture of one or two of coal gangue, gasified slag or fly ash in any proportion; the industrial solid waste B is a mixture of one or more of waste glass, iron tailings or silica ash in any proportion.
4. The lightweight pressure-resistant, heat-insulating and noise-reducing material according to claim 1 is characterized in that: The auxiliary material is a raw material rich in alkali metal and alkaline earth metal oxides.
5. The lightweight pressure-resistant, heat-insulating and noise-reducing material according to claim 4 is characterized in that: The auxiliary material is one of diatomaceous earth, albite, dolomite or talc, or a mixture of two or more of them in any proportion.
6. The lightweight pressure-resistant, heat-insulating and noise-reducing material according to claim 1, characterized in that: The additives include one or more of silicon carbide, sodium phosphate, polyvinyl alcohol, borax, sodium carbonate, and basic magnesium carbonate.
7. A method for preparing the lightweight pressure-resistant, heat-insulating and noise-reducing material according to any one of claims 1 to 6, comprising the following steps: 1) According to the chemical composition of industrial solid waste A, determine the selection and proportion of industrial solid waste A, industrial solid waste B, auxiliary materials and additives; 2) Dry ball milling the mixed raw materials to a particle size D90 < 45 μm to obtain a uniformly mixed powder; 3) spray drying the powder and preparing a molded embryo by stacking; 4) The formed embryo body is sintered at high temperature for a period of time in an air atmosphere by using a gradient program temperature rise sintering process, and then naturally cooled to room temperature to obtain a heat insulation, noise reduction, thermal insulation material.
8. The preparation method according to claim 7, characterized in that: In step 3), the step of preparing the shaped embryo body by the stacking method is: spraying the powder obtained in step 2) and drying it to constant weight to obtain particles with uniform particle size, transferring them to a mold, and flattening the surface to obtain a shaped embryo body.
9. The preparation method according to claim 7, characterized in that: The gradient program temperature rise sintering process is to increase the temperature from room temperature to 800-1100°C at 3-8°C / min, keep the temperature for 10-30 min, increase the temperature from 800-1100°C to 1120-1230°C at 0.5-5°C / min, and keep the temperature for 5-60 min.
10. Use of the lightweight compression-resistant heat-insulating and noise-reducing material according to any one of claims 1 to 6 as a thermal insulation and noise-reducing material.
Citation Information
Patent Citations
Preparation method of titanate porous thermal insulation material
CN101723701A
Preparation method of porous carbon heat-insulating composite material
CN106478124A
Lightweight porous thermal insulation material and preparation method thereof
CN108484119A
Cited By
Low-cost and high-performance cordierite honeycomb ceramic carrier and preparation method thereof
CN119683982A
Cordierite-based foamed ceramic prepared from industrial solid waste and preparation method thereof
CN121318518A
Multi-source solid waste synergistically modified gradient structure heat storage material and low-temperature preparation method
CN122104156A